Understanding the diversity of the metal-organic framework ecosystem - Seyed Mohamad Moosavi (Nature Portfolio, 2020)
At present there are databases with over 500,000 predicted or synthesized MOF structures, yet a method to establish whether a new material adds new information does not exist. Here the authors propose a machine-learning based approach to quantify the structural and chemical diversity in common MOF databases.